Resolution of Cutaneous Leishmaniasis and Persistence of Leishmania major in the Absence of Arginase 1 - Paduch, Katrin; Debus, Andrea; Rai, Baplu; Schleicher, Ulrike; Bogdan, Christian (Journal of Immunology, 2019)
Arginase (Arg) 1 is expressed by hematopoietic (e.g., macrophages) and nonhematopoietic cells (e.g., endothelial cells) and converts L-arginine into ornithine and urea. The enzyme is implicated in tissue repair but also antagonizes the production of NO by type 2 NO synthase in myeloid cells and thereby impedes the control of intracellular parasites such as Leishmania major. In this study, we tested whether Arg1 is required for spontaneous healing of acute cutaneous leishmaniasis in C57BL/6 mice and for lifelong parasite persistence in draining lymph nodes (dLNs) of healed mice. In vitro, bone marrow-derived macrophages and lymphoid endothelial cells readily expressed Arg1 in response to IL-4 and/or IL-13, whereas skin or dLN fibroblasts failed to do so, even during hypoxia. In vivo, Arg1 was found in skin lesions and, to a much lower extent, also in dLNs of acutely infected C57BL/6 mice but became undetectable at both sites after healing. Deletion of Arg1 in hematopoietic and endothelial cells using Tie2Cre(+/-) Arg1(fl/fl) C57BL/6 mice abolished the expression of Arg1 in skin lesions and dLNs but did not affect development and resolution of skin lesions, parasite burden, NO production, or host cell tropism of L. major during the acute or persistent phase of infection. Similar to wild-type controls, parasites persisting in Arg1-deficient mice favored NO synthase 2-negative areas and mainly resided in myeloid cells and fibroblasts. We conclude that Arg1 expression by hematopoietic and endothelial cells is completely dispensable for clinical resolution of cutaneous leishmaniasis and for long-term persistence of L. major.
CRIS-Team WoS Importer:2019-03-06

TNF-Mediated Restriction of Arginase 1 Expression in Myeloid Cells Triggers Type 2 NO Synthase Activity at the Site of Infection - Schleicher, Ulrike; Paduch, Katrin; Debus, Andrea; Obermeyer, Stephanie; Koenig, Till; Kling, Jessica C.; Ribechini, Eliana; Dudziak, Diana; Mougiakakos, Dimitrios; Murray, Peter J.; Ostuni, Renato; Koerner, Heinrich; et al. (Cell Reports, 2016)
Neutralization or deletion of tumor necrosis factor (TNF) causes loss of control of intracellular pathogens in mice and humans, but the underlying mechanisms are incompletely understood. Here, we found that TNF antagonized alternative activation of macrophages and dendritic cells by IL-4. TNF inhibited IL-4-induced arginase 1 (Arg1) expression by decreasing histone acetylation, without affecting STAT6 phosphorylation and nuclear translocation. In Leishmania major-infected C57BL/6 wild-type mice, type 2 nitric oxide (NO) synthase (NOS2) was detected in inflammatory dendritic cells or macrophages, some of which co-expressed Arg1. In TNF-deficient mice, Arg1 was hyperexpressed, causing an impaired production of NO in situ. A similar phenotype was seen in L. major-infected BALB/c mice. Arg1 deletion in hematopoietic cells protected these mice from an otherwise lethal disease, although their disease-mediating T cell response (Th2, Treg) was maintained. Thus, deletion or TNF-mediated restriction of Arg1 unleashes the production of NO by NOS2, which is critical for pathogen control.
EVALuna2:7700